2011
DOI: 10.1158/1078-0432.ccr-10-2047
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Infiltrating Macrophages Are Associated with Metastasis Suppression in High-Grade Osteosarcoma: A Rationale for Treatment with Macrophage Activating Agents

Abstract: Purpose: High-grade osteosarcoma is a malignant primary bone tumor with a peak incidence in adolescence. Overall survival (OS) of patients with resectable metastatic disease is approximately 20%. The exact mechanisms of development of metastases in osteosarcoma remain unclear. Most studies focus on tumor cells, but it is increasingly evident that stroma plays an important role in tumorigenesis and metastasis. We investigated the development of metastasis by studying tumor cells and their stromal context.Experi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
341
5
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 390 publications
(392 citation statements)
references
References 45 publications
19
341
5
2
Order By: Relevance
“…Clinicopathologic data of 51 patients with osteosarcoma are shown in Supplementary Table S1. Part of the samples was previously described (26). Biopsies were taken before preoperative chemotherapeutics were administered.…”
Section: Patient Materialsmentioning
confidence: 99%
“…Clinicopathologic data of 51 patients with osteosarcoma are shown in Supplementary Table S1. Part of the samples was previously described (26). Biopsies were taken before preoperative chemotherapeutics were administered.…”
Section: Patient Materialsmentioning
confidence: 99%
“…Approximately 30% of the patients with OS present clinically detectable metastatic disease at diagnosis (Kaste et al, 1999;Kager et al, 2003). So far, researchers have not thoroughly investigated treatment methods that could significantly increase survival, excluding preoperative chemotherapy (Buddingh et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 53 high-grade osteosarcomas, the number of CD14-positive TAMs was associated with reduced metastasis and improved survival, whereas the phenotype CD14/CD163 did not show this relationship 18 . The significance of CD68 and CD163 positive cells was also investigated in 149 samples of leiomyosarcomas.…”
Section: Discussionmentioning
confidence: 90%
“…[13][14][15][16] ). On the other hand, some studies have identified the effect of TAMs as tumor-suppressing [17][18][19][20] . This heterogeneity of the results is caused by the inability to clearly distinguish between TAM subtypes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation